Urban design for sustainability: A study on the Turkish city - Oktay, D (Taylor & Francis Inc, 2004)
In line with sustainable development principles, the reactions to modern architecture and planning have led to a new appreciation of traditional cities and urban environments. Considering the extensive neglect and devastation of local values in our cities and towns, urban development practice in Turkey cannot be said to meet the requirements of sustainability. This paper, therefore, will explore the logic of sustainable development and focus on the components of good urban design which are needed to produce it. Since promoting sustainable lifestyles in our towns and cities depends mainly on the design of the physical environment, the paper will propose a set of key design principles that can deliver sustainable urban development through exploring the qualities of,traditional urbanism' in the Turkish cities as well as examining the latest approaches to urban design.
CIB Tokyo Conference 2002 -- SEP 25-27, 2002 -- Tokyo, JAPAN
Keywords: sustainable development; compactness; combination with nature; sustainable movement patterns and public spaces; community development; Turkish city